Infertility and vaginal microbiome: review study - Oliveira, Muse Santiago de; Medeiros, Francisco das Chagas; Eleutério Junior, José (Brazilian Journal of Sexually Transmitted Diseases, 2019)
Introduction: Infertility is an important public health problem and has many causal factors. Previous findings, based mainly on culture techniques, suggest an association between infertility and changes in the vaginal microbiome. The metagenomic approach allowed the discovery of new bacterial species, previously unidentified in the female genital tract, permitting a deeper knowledge of the role of vaginal microbiome in female reproductive health. Objective: To evaluate the association of changes in the vaginal microbiota with infertility, and its repercussions on the outcome of assisted reproduction techniques after a decade of the Human Microbiome Project. Methods: A systematic search was carried out in the MEDLINE database between September and November 2018, by selecting 14 studies, associating vaginal microbiome with infertility, or with results of assisted reproduction techniques. Results: The findings showed a higher prevalence of bacterial vaginosis, and increased microbial diversity in the vagina of infertile women. Regarding the success of assisted reproduction techniques, most studies did not show any significant association between bacterial vaginosis and reduction in pregnancy rates. Conclusion: Further studies are needed to better understand the influence of the balance of vaginal microorganism species on female reproductive health, addressing the microbiome composition in contexts beyond in vitro fertilization techniques.